Simulasi penerapan looping system JTR untuk meningkatkan layanan pelanggan PT. PLN (Persero) menggunakan perangkat lunak ETAP - I Putu Sutawinaya; I Wayan Sudiartha; I Ketut Ta; I Gede Guntur Saputra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
In the process of implementing a looping low-voltage network. In this study, the author analyzes the application looping of low-voltage networks in premium bronze customers which is applied to the DB0575 and DB0292 substations. There are several things that are analyzed in this study, namely transformer loading, voltage drop, loading of KHA, analysis of the best networks, and protection of NH Fuse. This research uses software in simulating the application looping of low-voltage networks. Transformer loading before the application of looping low voltage networks on DB0575 and DB0292 are 28.2% and 48.95% while after the application of looping of low-voltage networks are 28.2% and 51.9%. The smallest value of voltage drop and loading of KHA are resulted in the 1st direction at the DB0575 substation with a value of 1.17% and 7.08% and the 4th direction at the DB0292 substation with a value of 0.73% and 17.91%, And the recommended protection rating for the DB0575 substation after the application is using the NH Fuse 'gG' rated current 200 A with a maximum voltage of 690 V and a rated breaking capacity of 50 kA as a protection system on low voltage distribution panel for a 3-phase 250 kVA 2-way distribution transformer. Meanwhile, the DB0292 substation uses an NH Fuse 'gG' rated current 125 A with a maximum voltage of 690 V and a rated breaking capacity of 50 kA as a protection system on low voltage distribution panel for a 3-phase 315 kVA 4-way distribution transformer.